The expression pattern of GDF15 in human brain changes during aging and in Alzheimer’s disease - Chiariello, Antonio; Valente, Sabrina; Pasquinelli, Gianandrea; Baracca, Alessandra; Sgarbi, Gianluca; Solaini, Giancarlo; Medici, Valentina; Fantini, Valentina; Poloni, Tino Emanuele; Tognocchi, Monica; Arcaro, Marina; Galimberti, Daniela; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction Growth Differentiation Factor 15 (GDF15) is a mitochondrial-stress-responsive molecule whose expression strongly increases with aging and age-related diseases. However, its role in neurodegenerative diseases, including Alzheimer’s disease (AD), is still debated. Methods We have characterized the expression of GDF15 in brain samples from AD patients and non-demented subjects (controls) of different ages. Results Although no difference in CSF levels of GDF15 was found between AD patients and controls, GDF15 was expressed in different brain areas and seems to be predominantly localized in neurons. The ratio between its mature and precursor form was higher in the frontal cortex of AD patients compared to age-matched controls (p < 0.05). Moreover, this ratio was even higher for centenarians (p < 0.01), indicating that aging also affects GDF15 expression and maturation. A lower expression of OXPHOS complexes I, III, and V in AD patients compared to controls was also noticed, and a positive correlation between GDF15 and IL-6 mRNA levels was observed. Finally, when GDF15 was silenced in vitro in dermal fibroblasts, a decrease in OXPHOS complexes transcript levels and an increase in IL-6 levels were observed. Discussion Although GDF15 seems not to be a reliable CSF marker for AD, it is highly expressed in aging and AD brains, likely as a part of stress response aimed at counteracting mitochondrial dysfunction and neuroinflammation.